Feminist Stylistics in Boston Strangler (2023): Women’s Struggle for Equality in Media Representation - Rusida, Elizabeth; Tambunan, Friska; Aprianti, Thesia; Rangkuti, Rahmadsyah (Universitas Muhammadiyah Mataram, 2025)
This study aims to analyze the gender dynamics reflected in the film Boston Strangler (2023) using a qualitative by feminist stylistics approach. The research examines how the film's linguistic representation reflects the challenges and progress of women in investigative journalism. By employing linguistic and stylistic analysis, the study identifies language choices, sentence structures, and discourse patterns that either reinforce or challenge traditional gender constructs in the media. The findings reveal that at the lexical level, the film often depicts men as authoritative figures, while women are portrayed as emotional or excessive in asserting their professionalism. Sentence structures further emphasize gender inequalities, with female characters frequently having to justify their abilities in the workplace. On a broader discourse level, while the film highlights the structural barriers faced by women in male-dominated fields, it also showcases their resilience in challenging societal expectations. This study underscores the significance of language in shaping gender perceptions and provides deeper insights into the representation of women in the media. It also contributes to broader discussions on the portrayal of women on screen and the role of media in shaping social norms. Future research could explore similar linguistic patterns in other films within the same genre to observe the evolving portrayal of gender in cinema.